Relationship Between Arm Span Measurements and Body Height in Bar - Katarina Dragutunovic (Journal of Anthropology of Sport and Physical Education, 2018)
The aim of this study was to examine the body height of Montenegrin adolescents from Bar, as well as the relationship between the arm span and body height, as a possible predictor of body height. The research was conducted on 101 Montenegrin adolescents from the southern region of Montenegro, of which 50 are men of average age 18.28 ± 0.64 years and 51 girls of the average age of 18.43 ± 0.67 years. Anthropometric measurements were carried out in accordance with the International Society for the Improvement of Kinanthropometry (ISAK) protocol. The correlation between body height and arm span was done by a correlation analysis with a confidence of 95%. Then, a linear regression analysis was performed to examine the degree to which the range of arm span can reliably predict growth. The results show that male adolescents are 182.13 ± 7.47 cm high and have arm span of 185.22 ± 9.02 cm, while girl adolescents are 168.95 ± 6.79 cm high and have arm span of 167.03 ± 7.87 cm. Compared to other studies, the results showed that both sexes from Bar highest above the majority of the nation across Europe. On the other hand, the range of arm span reliably predicts the height of the body in this part of Montenegro, at both sexes. This research was carried out due to the need to create a special height model for each region in Montenegro.